Design an Android-based Applications called “BEVENTS!” as Event Promotion Platform in Bandung - Mustafa Afandi; Dani Hamdani (Association for Scientific Computing Electrical and Engineering, 2020)
Bandung, as a creative city, has made many event organizers that want to hold an event in Bandung. More event organizers are popping up, and there will be many events in Bandung. However, the lack of media that can promote and informs events makes people less aware of information about any events due to lack of thorough event reporting in Bandung. People who want to attend an event are required to buy a ticket which is usually done directly on the spot, which sometimes makes them lazy because of long queues, so they need a system to assist event organizers in promoting events and selling event tickets online, which can simplify the process of booking event tickets to make it easier and more precise. Also, it can provide detailed information from an event in Bandung. In this research, the author tries to design an android-based application called “BEVENTS!” to make it easier for event organizers to promote and sell event tickets. Besides, this application also responds to problems that occur in the ticket booking process manually, which will make it easier for event enthusiasts to order tickets online through smartphones. With “BEVENTS!”, the author hopes that help event organizers to spread quickly of event information, so that it makes it very easy for the public to know about available events in Bandung. From the results of this research, the applications can run well, and the current system does not display an error. This application can connect the event organizers with people who interest the event in one platform.